Exploring the affective underpinnings of dynamic managerial capabilities - Huy, Quy; Zott, Christoph (Strategic Management Journal, 2019)
[Research Summary: Our inductive field study identifies specific emotion regulation (ER) actions as affective underpinnings of dynamic managerial capabilities. ER refers to the management and modification of one's own and other people's emotions for a specific purpose. Our study shows how differences in managers' attention to ER influence the extent to which they can mobilize resources to pursue market opportunities. We show how their ER of the self helps them mobilize human capital resources by creating psychic benefits, whereas their ER of others helps mobilize social capital by facilitating legitimacy judgments. Our emerging theory explains how the capacity for ER constitutes an important foundation of dynamic managerial capabilities and how it is linked with other key conceptual underpinnings of the construct, namely managerial human and social capital. Managerial Summary: Strategic change processes can be full of ups and downs and have been likened to an emotional roller coaster. In this context, senior managers do not only to have to cope with their own emotions to deal with challenging situations; they also have to pay attention to the emotions of other stakeholders such as employees and investors to maintain or gain these stakeholders' support. Our field study identifies and explains the systematic behaviors that senior managers can use in strategic change contexts to regulate their own emotions as well as those of other stakeholders in order to productively address and overcome difficult business conditions.]